Evidence for contemporary plant mitoviruses - Nibert, Max L.; Vong, Minh; Fugate, Karen K.; Debat, Humberto Julio (2018)
Mitoviruses have small RNA(+) genomes, replicate in mitochondria, and have been shown to infect only fungi to date. For this report, sequences that appear to represent nearly complete plant mitovirus genomes were recovered from publicly available transcriptome data. Twenty of the refined sequences, 2684–2898 nt long and derived from 10 different species of land plants, appear to encompass the complete coding regions of contemporary plant mitoviruses, which furthermore constitute a monophyletic cluster within genus Mitovirus. Complete coding sequences of several of these viruses were recovered from multiple transcriptome (but not genome) studies of the same plant species and also from multiple plant tissues. Crop plants among implicated hosts include beet and hemp. Other new results suggest that such genuine plant mitoviruses were immediate ancestors to endogenized mitovirus elements now widespread in land plant genomes. Whether these mitoviruses are wholly cryptic with regard to plant health remains to be investigated.